Equity Concentration and Inefficient Investment: -- Empirical Evidence from Listed Companies in China - Xie, Siyi (Transactions on Economics, Business and Management Research, 2024)
Enterprise investment efficiency has been a hot topic of concern to all walks of life, and equity concentration, as an important element of corporate governance and modern enterprise construction, has attracted extensive attention from the academic community. Hence, this paper provides theoretical analyses and empirical tests on the relationship between corporate inefficient investment and equity concentration. After regression analysis, this paper finds that there is a significant negative relationship between equity concentration and the degree of inefficient investment, which confirms the hypothesis that equity concentration reduces the level of inefficient investment; compared to the company with CEO duality, in the case of equity concentration, the separation of decision-making power and decision-controlling power is more able to reduce the level of inefficient investment; However, the allocation of decision-making power does not have a significant effect on this relationship mechanism. This paper provides  some theoretical basis and implications for how enterprises can optimise their shareholding structure and promote the reform of corporate governance modernisation so as to enhance investment efficiency.